The Role of ESG Disclosure in Enhancing Financial Statement Transparency of Indonesian Public Companies - Silaban, Barnabas Tridig (Institut Bisnis dan Informatika Kesatuan, 2025)
In recent years, environmental, social, and governance disclosures have gained attention for their role in improving the transparency of financial statements, particularly in emerging markets like Indonesia. This study aims to explore how these disclosures enhance the clarity and reliability of financial reports for public companies listed on the Indonesia Stock Exchange. Using a qualitative approach, the study analyzes the 2023 annual reports of 30 companies from sectors such as mining, manufacturing, and financial services, guided by the Global Reporting Initiative framework. The findings show that detailed disclosures on environmental initiatives, social programs, and governance practices provide clearer insights into financial risks and opportunities, making financial statements more understandable. Companies with high-quality disclosures, such as specific metrics on carbon emissions or anti-corruption policies, are perceived as more transparent by stakeholders. This study concludes that comprehensive environmental, social, and governance disclosures significantly improve financial transparency in Indonesia, supporting investor trust and sustainable practices. These insights offer practical guidance for companies to enhance their reporting and for regulators to develop stronger guidelines.